P523 Effectiveness of biological treatments for inflammatory bowel disease in the elderly patients. (21st January 2022) - Suarez Ferrer, C J; Mesonero, F; Caballol, B; Ballester, M P; Baston Rey, I; Castaño Garcia, A; Miranda Bautista, J; Saiz Chumillas, R; Benitez, J M; Sanchez Delgado, L; Lopez-Garcia, A; Rubin de Celix, C; et al.
Abstract: Background: Biological treatments used for the treatment of inflammatory bowel disease (IBD) have demonstrated their efficacy and safety, although these results were obtained from studies that mostly include young people generally included in clinical trials. The objective of our study is to assess the efficacy of these treatments in the elderly population in real life Methods: Patients have been retrospectively included with established diagnosis of IBD aged 65 years or older at the time of initiating biological treatment(Infliximab, Adalimumab, Golimumab, Ustekinumab or Vedolizumab).Among the patients included, the clinical response (at the discretion of the researcher)after induction(around 12 weeks of treatment)and at 52 weeks was assessed.When that were available, the data related to endoscopic response at week 52 were collected(endoscopic activity was classified as moderate, mild or severe, according to the researcher) Results: A total of 1090 patients were included(707 CD and 383 UC).The indication for biologic in our experience was lack of response to immunosuppressants(292, 27.1%), corticodependence(318, 29.5%), perianal disease(31, 2.9%), treatment for postoperative recurrence(76, 7.0%), severe corticorefractory ulcerative colitis(59, 5.5%), others(303, 28.1%).After induction, at approximately 12–14 weeks of treatment, 419(39.6%) were in clinical remission, 502(47.4%) had a response without remission, and 137 patients(12.9%) had no response.The percentages of remission with the different biologics were: infliximab 159 patients(42.6%), adalimumab 118 patients (38.4%), golimumab 9 patients(32.1%), ustekinumab 50(32.7%), vedolizumab 84(40.6%)(p = 0.3).At 52 weeks of treatment 442 patients(50.63%) clinical remission, 249 patients had a response (28.5%) and 53 patients had no response (6.1%). Before one year of treatment, 129 patients(14.8%) had suspended treatment due to ineffectiveness, being significantly higher(p <0.0001) for golimumab 9 patients(37.5%) compared to the rest of the biological treatments analyzed.We analyzed the percentages of clinical response to the different biological treatments, without identifying statistically significant differences between the remission rates: infliximab 160 (51.3%), adalimumab 131(50.9%), golimumab 10(41.7%), ustekinumab 49(44.9%) and vedolizumab 92(53.8%).In colonoscopy at 52 weeks(performed 218 patients), 35.8% endoscopic remission(78 patients), 32.1% mild activity(70 patients), 26.1% moderate activity(57 patients) and 6.0% severe activity(13 patients). Conclusion: Biological drugs have response rates in elderly patients similar to those described in the general population. In our experience, golimumab was the drug that had to be discontinued most frequently due to ineffectiveness.